2011
DOI: 10.1002/ejoc.201001588
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Pd‐Catalyzed Reactions of Diazo Compounds

Abstract: Pd‐catalyzed reactions of diazo compounds result in unique transformations that are distinct from those of traditional processes catalyzed by RhII or CuI catalysts. Pd carbene migratory insertion was deemed to be the key step in a series of Pd‐catalyzed reactions of diazo compounds. The combination of this unique reaction and classic Pd‐catalyzed cross‐coupling provides new potential for the development of novel Pd‐catalyzed transformations, in particular for C=C double bond formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
90
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(91 citation statements)
references
References 123 publications
1
90
0
Order By: Relevance
“…[8] During the last decade, a number of contributions relating to the use of diazomethane as a carbene reagent with palladium-based catalysts have appeared, [9] a topic recently reviewed by Wang and Zhang. [10] However, such catalysts seem to fail with alkyl diazoacetates as the reactant, [9a, b, 11] in spite of the fact that they are stable and either commercially available or easy-to-prepare reagents, in contrast to diazomethane, which is known to be unstable.…”
Section: Introductionmentioning
confidence: 99%
“…[8] During the last decade, a number of contributions relating to the use of diazomethane as a carbene reagent with palladium-based catalysts have appeared, [9] a topic recently reviewed by Wang and Zhang. [10] However, such catalysts seem to fail with alkyl diazoacetates as the reactant, [9a, b, 11] in spite of the fact that they are stable and either commercially available or easy-to-prepare reagents, in contrast to diazomethane, which is known to be unstable.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] In the past few years, a novel type of palladium-catalyzed cross-coupling reactions involving carbene migratory insertion process has emerged as a powerful method for the construction of C-C double bonds. [10][11][12][13][14] As shown in Scheme 1a, palladium-catalyzed cross-coupling reaction based on carbene migratory insertion includes the following common processes: 15 (1) metal species A is captured by the diazo compound to generate metal carbene species B; (2) migratory insertion occurs to produce a new metal species C which undergoes further transformations, typically β-hydride elimination; (3) the reaction releases coupling product D and regenerates the metal catalyst. According to this sequence, various alkene formation reactions have been designed and developed.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Recent studies showed that Pd 0/II complexes can catalyze reactions of carbenes generated from aryl diazomethanes or alkyl diazomethanes to give cross-coupling products. [4] A major challenge in metal-catalyzed alkyl carbene C À H insertion/transfer reactions is the low stability of alkyl diazomethanes, which are the common source of alkyl carbenes. To circumvent this difficulty, Morandi and Carreira reported the in situ generation of diazomethane from a water-soluble diazald derivative for the cyclopropanation of alkenes.…”
mentioning
confidence: 99%